Comparative Study on the Presence of Historical Thinking Skills in the Educational Curricula of Different Countries - Martínez-Hita, María (2022)
Introduction. Historical thinking is a highly relevant aspect in teaching-learning history as it is a didactic approach that allows the development of more complex cognitive skills from a constructivist perspective. For students’ historical education to be based on this teaching approach, it is necessary to introduce it into educational curricula, among other aspects. Method. This qualitative research aimed to compare the curricula of ten countries (Canada, the United States, Mexico, Chile, Argentina, Australia, England, Portugal, France, and Spain), of particular relevance for their publications on this subject, to verify the presence of historical thinking concepts in them through the technique of content analysis. Results. The results showed that these concepts were incorporated into most curricula according to educational studies conducted on this subject. The results showed that most of the curricula have echoed the educational research carried out on this theme, including such concepts in their study programs. Discussion. Nevertheless, some modifications are necessary in the study programs of other countries to foster the development of historical thinking among students. To this end, curricula in which the historical concepts proper to this teaching approach are fully integrated can serve as a model and reference.